Multiple-criteria analysis as a method for defining medium-sized cities - Živanović, Zora (Geodetski vestnik, 2015)
Decentralization and the inclination towards a balanced regional development bring about a redistribution of cities% functions: certain responsibilities are transferred from centres at higher hierarchy levels to regional centres (mostly medium-sized cities). In this context, the authors have analysed the importance of medium-sized cities in the settlement network and discussed the issue of their identification within the national urban system. The purpose of this study is to establish a method for the identification of the set of medium-sized cities within the network of urban settlements, with particular reference to Central Serbia. The authors also compare the method with the one used in Slovenia in order to demonstrate that the phrase "medium-sized city" may have different meanings depending on the context in which it is defined. Along with the demographic size as the most important indicator in defining medium-sized cities, economic, social, functional, infrastructural and institutional criteria have also been taken into consideration.
Keywords: geografija naselij; mesta; omrežje naselij; policentrični razvoj; polycentrc development; Serbia; settlement geography; settlement network; Slovenia; Slovenija; Srbija; urban geography